An association between the rs1799853 and rs1057910 polymorphisms of CYP2C9, the rs4244285 polymorphism of CYP2C19 and the prevalence rates of drug-resistant epilepsy in children. (2nd December 2021) - Makowska, Marianna; Smolarz, Beata; Bryś, Magdalena; Forma, Ewa; Romanowicz, Hanna
Abstract: Objective: Epilepsy is a neurologically based disease. Literature data indicate a certain association between the polymorphism of these genes, which participate in the metabolism of drugs (CYP), and drug-resistant epilepsy. Aim: The reports describe studies in which an association was evaluated between the rs1799853 (430C > T) and rs1057910 (1075A > C) polymorphisms of CYP2C9 gene and the rs4244285 (c.681G > A) polymorphism of CYP2C19 gene on one hand and the incidence of drug-resistant epilepsy in children on the other. Material and methods: The above-mentioned polymorphisms were assessed by the PCR-RFLP technique in a group of patients with drug-resistant ( n  = 106) and drug-responsive ( n  = 80) epilepsy, as well as in non-epileptic children ( n  = 97), all of them hospitalised at the Department of Neurology of the Institute-Polish Mother's Memorial Hospital in Lodz. Results: It was demonstrated that CT genotype of the rs1799853 polymorphism of CYP2C9 gene and GA genotype of the rs4244285 polymorphism of CYP2C19 gene caused an enhanced risk of epilepsy. It was also shown that the occurrence of C-G-A haplotype, when referred to the rs1799853 polymorphism of CYP2C9 gene and the rs4244285 polymorphism of CYP2C19 gene, could be associated with a decreased risk of epilepsy occurrence. In case of the rs1799853 polymorphism in CYP2C9 gene, the occurrence of T allele four times increases the risk of drug-resistance in patients with diagnosed epilepsy. Conclusion: The obtained results indicated that the rs1799853 and rs1057910 polymorphisms of CYP2C9 gene and the rs4244285 polymorphism of CYP2C19 gene could be associated with the occurrence of drug-resistant epilepsy in children.